2014
DOI: 10.1186/1743-0003-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Systematic changes in position sense accompany normal aging across adulthood

Abstract: BackgroundDevelopment of clinical neurological assessments aimed at separating normal from abnormal capabilities requires a comprehensive understanding of how basic neurological functions change (or do not change) with increasing age across adulthood. In the case of proprioception, the research literature has failed to conclusively determine whether or not position sense in the upper limb deteriorates in elderly individuals. The present study was conducted a) to quantify whether upper limb position sense deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 60 publications
(80 reference statements)
6
112
1
Order By: Relevance
“…Overall, these results are strongly in line with the current field of knowledge on proprioceptive acuity in older age. Specifically, several other investigators have reported an age-related decline in motion (Kokmen et al 1978;Wright et al 2011) and position sense of the upper limbs (Adamo et al 2007;Adamo et al 2009;Herter et al 2014). These deteriorations may partially be caused by physiological changes in the structure and function of muscle spindles throughout late adulthood (Herter et al 2014;Kalisch et al 2012;Proske and Gandevia 2012).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Overall, these results are strongly in line with the current field of knowledge on proprioceptive acuity in older age. Specifically, several other investigators have reported an age-related decline in motion (Kokmen et al 1978;Wright et al 2011) and position sense of the upper limbs (Adamo et al 2007;Adamo et al 2009;Herter et al 2014). These deteriorations may partially be caused by physiological changes in the structure and function of muscle spindles throughout late adulthood (Herter et al 2014;Kalisch et al 2012;Proske and Gandevia 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, there was no evidence to show that the withdrawal of visual feedback increased aiming errors in the non-active older adults more than in the other three groups, even though the proprioceptive ability of this group was, generally, inferior (negating hypothesis 3). Those seemingly contradicting outcomes require further attention because main body of findings from both experiments are consisted with a vast body of literature on effects of physical activity and aging on manual aiming (e.g., Chaput and Proteau 1996;Lyons et al 1996;Seidler-Dobrin and Stelmach 1998;Van Halewyck et al 2014) and proprioception (e.g., Adamo et al 2007;Adamo et al 2009;Herter et al 2014;Wright et al 2011). The specific effects of age and physical activity level on manual aiming and proprioception as emerged in findings of experiment 1 and experiment 2 are discussed in more details next.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visually guided reaching (VGR) assesses visuomotor abilities by having participants perform center‐out reaching 28. Position matching (PM) is a test of proprioception (position sense), in which the robot moves the stroke‐affected arm to 1 of 9 locations, and the subject is instructed to move their other arm to the mirror‐image location with vision occluded 29, 30. Object hit (OH) is a test of bimanual sensorimotor control in which participants use virtual paddles at their fingertips to hit away balls that move toward them at increasing speed and frequency 31.…”
Section: Methodsmentioning
confidence: 99%